Violencia de Estado y literatura en Argentina (1973-2003) - Carolina Rocha (Amnis)
The purpose of this article consists of showing the resistance that is done, being it as denunciation or reflection, from the realm of literary creation. For that, I will examine the different forms that state violence acquires in the works of Argentine authors through a chronological analysis that focuses on the last thirty years. Therefore, I will describe how state violence changes in form and how it appears as themes or metaphors in five texts : Aquí pasan cosas raras (1975) by Luisa Valenzuela, La casa y el viento (1984) by Héctor Tizón, La convaleciente (1987) by Pedro Orgambide, La madriguera (1996) by Tununa Mercado y A los que se van (2002) by Alicia Dujovne Ortiz.